Theatre Beyond Nationalism: Participatory Art in the Cyprus Buffer Zone - Evangelou, Ellada (My University, 2019)
The turbulent 20th century has left Cyprus with contested spaces scattered around its terrain. The period of inter-communal violence and ensuing war have left its two main ethnic communities living on each side of a buffer zone, which separates the island into two parts. Identity within the communities presents interesting trends, with the Greek Cypriot community (the focus of this study) developing a locally cultivated Greek nationalism, as well as Cypriotism at a later stage, both of which have rendered the buffer zone into a non-space. Through this paper, I propose that since 2011, the buffer zone offers an alternative understanding of community, through the participatory art that takes place there. Through the mechanisms of collaborative creation, the generation of new, temporary communities, which are engaged with social issues, and the focus on both process and result, new conversations arise, and new priorities are set within the artistic realm. Two plays are used as case studies, Shift, by Rooftop Theatre and Gülgün Kayim and BAM!, by Giorgos Neophytou, produced by Paraplevros Productions, which were presented within the buffer zone in 2014 and 2017 respectively, and grounded within and interacting with the buffer zone and its temporary communities, generating a new dialectic.
Keywords: Participatory art; Buffer Zone; Dialectic; Theater; Identity